Effect of Electrode and Current Variation of Smaw Welding With V-ShapeOn the Bending Strength of ASTMA36 Ship Steel Plate Material - Regi Septian Permadi; Erifive Pranatal (National Research and Innovation Agency (BRIN Publishing), 2024)
This study aims to analyze the effect of current and type of electrode on bending strength with V-shoulder and using SMAW (Shielded Metal Arc Welding) welding on ASTM A36 steel plate. The SMAW welding method was chosen because of its wide use in the industrial field, one of which is in the field of steel ship construction. The welding process is carried out with current variations of 90A, 100A and 130A and the types of electrodes used are AWS E6013 and AWS E7016. Bending tests were conducted using relevant ASME Section IX standards to evaluate the strength and ductility of the joints. After obtaining data from the test results of several samples from different electrodes with different currents, the average value is obtained, namely, the sample using the E7016 electrode with a current of 100A is 1771,63 MPa, the sample using the E6013 electrode with a current of 90A is 1485,21 MPa. From these results it can be concluded that there is a difference in bending strength between each specimen, which indicates that variability in test conditions, such as current variation and electrode variation, is an important role in influencing the final results in bending testing. Experimental studies are carried out by testing bending on specimens that have been welded with welding current and electrode.